Epigenetic Delay in the Neurodevelopmental Trajectory of DNA Methylation States in Autism Spectrum Disorders - Corley, Michael J.; Vargas-Maya, Nauru; Pang, Alina P. S.; Lum-Jones, Annette; Li, Dongmei; Khadka, Vedbar; Sultana, Razvan; Blanchard, D. Caroline; Maunakea, Alika K. (Frontiers in Genetics, 2019)
Autism spectrum disorders (ASD) are hypothesized to originate in utero from perturbations in neural stem cell niche regions of the developing brain. Dynamic epigenetic processes including DNA methylation are integral to coordinating typical brain development. However, the extent and consequences of alterations to DNA methylation states in neural stem cell compartments in ASD are unknown. Here, we report significant DNA methylation defects in the subventricular zone (SVZ) of the lateral ventricles from postmortem brain of seventeen autism-diagnosed compared to seventeen age and gender-matched typically developing individuals. Both array- and sequencing-based genome-wide methylome analyses independently revealed that these alterations were preferentially targeted to intragenic and bivalently modified chromatin domains of genes predominately involved in neurodevelopment, which associated with aberrant pre-mRNA splicing events of ASD-relevant genes. Integrative analysis of our ASD and typically developing postmortem brain methylome datasets with that from fetal brain at different neurodevelopmental stages revealed that the methylation states of differentially methylated loci associated with ASD remarkably resemble the methylation states at earlier time points in fetal brain development. This observation was confirmed using additional methylome datasets from three other brain regions. Altogether, these findings implicate an epigenetic delay in the trajectory of normal DNA methylation states during the course of brain development that may consequently lead to deleterious transcriptomic events in ASD and support the hypothesis of an early developmental origin of ASD.